Adenocarcinoma of the lung. Issue 1 (January 1969) - Hinds, J. R.; Hitchcock, G. C.
Abstract : The clinical and histological features of 53 cases of adenocarcinoma of the lung are presented. In more than one-third of the patients the tumour was a solitary nodule, raising the possibility that it might be a metastatic focus. Although histological features may suggest an origin from such sources as the kidney, uterus, ovary or bowel, nearly all such cancers are, in fact, primary bronchial tumours. It is seldom justifiable to submit the patient with a nodular adenocarcinoma in the lung to a search for a possible extrathoracic primary neoplasm.